TRAINING TO ENHANCE TUTOR CAPACITY THROUGH THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN THE DEVELOPMENT OF TEACHING MATERIALS FOR UNIVERSITY PROFESSORS AND SCHOOL TEACHERS IN SOLOK, WEST SUMATRA - Agus Nurofik; Nini Nini; Dorris Yadewani; Lina Tio; Sutiyem Sutiyem; Yoserizal Yoserizal; Tri Irfa Indrayani (TOPLAMA, 2026)
The rapid development of Artificial Intelligence (AI) opens up significant opportunities for transforming the world of education, particularly in terms of the efficiency of creating instructional materials. However, many educators in rural areas, such as in Solok, West Sumatra, have not yet made optimal use of this technology due to limited digital literacy. This community service initiative aims to enhance the capacity of instructors (university lecturers and school teachers) in the City and Regency of Solok to design, create, and develop AI-based interactive teaching materials. The approach involves hands-on workshops combined with intensive mentoring. The AI applications covered in the training included ChatGPT for developing syllabi and text-based materials, Gamma.app for visual presentations, and Quizizz AI for learning assessment. The target audience consisted of 45 participants, comprising university lecturers and high school teachers in Solok. Evaluation results from pre- and post-tests showed a 64% increase in participants’ theoretical understanding and a 78% increase in practical skills. Additionally, 92% of participants successfully produced AI-based instructional modules ready for implementation. This initiative concluded that AI integration has proven capable of reducing the time required to produce instructional materials while simultaneously improving the visual quality and diversity of educators’ instructional content.